Concomitant activation of the PI3K/Akt and ERK1/2 signalling is involved in cyclic compressive force‐induced IL‐6 secretion in MLO‐Y4 cells. (10th January 2014) - Yin, Jian; Hao, Zhichao; Ma, Yuanyuan; Liao, Shuang; Li, Xianxian; Fu, Jing; Wu, Yeke; Shen, Jiefei; Zhang, Ping; Li, Xiaoyu; Wang, Hang
Abstract IL‐6 has a dual role in bone remodelling. The ERK1/2 pathway partially upregulated IL‐6 secretion in osteocyte‐like MLO‐Y4 cells exposed to CCF. We have now investigated the possible role of phosphatidylinositol 3‐kinase (PI3K)/Akt signalling pathway in the CCF‐induced IL‐6 expression. MLO‐Y4 cells were treated with CCF 2, 000 µstrain, 2 Hz, or 10, 30 min, 1, 3 and 6 h. IL‐6 expression, Akt and ERK1/2 and PI3K/Akt phosphorylation were determined by RT‐PCR, ELISA and Western blotting. Inhibition of PI3K/Akt with LY294002 or ERK1/2 with PD98059 significantly attenuated IL‐6 upregulation, and IL‐6 expression was abolished by inhibiting both pathways. Inhibition of one pathway downregulated the other's phosphorylation level. In conclusion, concomitant activation of PI3K/Akt and ERK1/2 pathways mediated IL‐6 expression in MLO‐Y4 cells under CCF.